2015
DOI: 10.1111/bph.13150
|View full text |Cite
|
Sign up to set email alerts
|

Spinal antinociceptive effects of the novel NOP receptor agonist PWT2‐nociceptin/orphanin FQ in mice and monkeys

Abstract: Background and purposeUsing an innovative chemical approach, peptide welding technology (PWT), a tetrabranched derivative of nociceptin/orphanin FQ (N/OFQ) has been generated and pharmacologically characterized. Both in vitro and in vivo PWT2‐N/OFQ displayed the same pharmacological profile to the natural ligand. It was more potent and produced longer‐lasting effects. The aim of the present study was to investigate the spinal effects of PWT2‐N/OFQ in nociceptive and neuropathic pain models in mice and non‐huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…More importantly, this largely increased potency and improved duration of action exhibited by PWT2-N/OFQ can be translated from rodents to primates. Intrathecal administration of PWT2-N/OFQ potently produced full antinociceptive effects lasted for more than 24 hours in monkeys (Rizzi et al, 2015). Under similar experimental conditions, PWT2-N/OFQ (0.3–3 nmol) is approximately 30-fold more potent than N/OFQ (10–100 nmol) and the duration of antinociceptive action of PWT2-N/OFQ (~24 hours) is 10-fold longer than that of N/OFQ (~2.5 hours) in primates (Ding et al, 2015b; Ko et al, 2006; Rizzi et al, 2015).…”
Section: Spinal Actions Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, this largely increased potency and improved duration of action exhibited by PWT2-N/OFQ can be translated from rodents to primates. Intrathecal administration of PWT2-N/OFQ potently produced full antinociceptive effects lasted for more than 24 hours in monkeys (Rizzi et al, 2015). Under similar experimental conditions, PWT2-N/OFQ (0.3–3 nmol) is approximately 30-fold more potent than N/OFQ (10–100 nmol) and the duration of antinociceptive action of PWT2-N/OFQ (~24 hours) is 10-fold longer than that of N/OFQ (~2.5 hours) in primates (Ding et al, 2015b; Ko et al, 2006; Rizzi et al, 2015).…”
Section: Spinal Actions Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
“…Intrathecal administration of PWT2-N/OFQ potently produced full antinociceptive effects lasted for more than 24 hours in monkeys (Rizzi et al, 2015). Under similar experimental conditions, PWT2-N/OFQ (0.3–3 nmol) is approximately 30-fold more potent than N/OFQ (10–100 nmol) and the duration of antinociceptive action of PWT2-N/OFQ (~24 hours) is 10-fold longer than that of N/OFQ (~2.5 hours) in primates (Ding et al, 2015b; Ko et al, 2006; Rizzi et al, 2015). It is worth noting that among all agonists selective for opioid receptor subtypes, NOP receptor agonists are the only class of drugs that are able to change the nociceptive threshold of primates without side effects commonly caused by MOP receptor agonists (Lin & Ko, 2013).…”
Section: Spinal Actions Of the N/ofq-nop Receptor Systemmentioning
confidence: 99%
“…The PWT has been applied to different peptide sequences including nociceptin/orphanin FQ (N/OFQ) (Rizzi et al, 2014; Rizzi et al, 2015), neuropeptide S (Ruzza et al, 2015), and tachykinins (substance P, neurokinin A and B) (Ruzza et al, 2014). These studies demonstrated that PWT derivatives maintained the in vitro pharmacological profile (pharmacological activity, potency and selectivity of action) of the parent peptide sequences while showing higher in vivo potency and particularly long lasting action.…”
Section: Introductionmentioning
confidence: 99%
“…route ultralow doses of N/OFQ (fmol) produced spontaneous agitation and painlike behavior in mice (Sakurada et al, 1999), whereas at nanomolar dose range produced antinociceptive effects clearly demonstrated by several laboratories (Lin and Ko, 2012;Micheli et al, 2015a;Rizzi et al, 2015). Recently, we compared the spinal antinociceptive properties of N/OFQ and two NOP peptide agonists developed by the University of Ferrara, UFP-112 and UFP-113 (full and partial NOP agonist, respectively; Arduin et al, 2007;Rizzi et al, 2007;Calò et al, 2011) antinociceptive action comparable to 1-3 nmol/h morphine or N/OFQ.…”
Section: Nop Receptor Agonists and Acute Painmentioning
confidence: 93%